Can We Reconcile The Universal Human Rights with Islam - Mirza Fahlevy (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
The Universal Human Rights is one of the most intrigued issues and often hotly being discussed around the globe. The issue seems never escape from media. This is not because the Human Rights is irrelevant to the human being, rather its value isessential. Several countries, for example, shift human rights discourses when drafting certain bill before passing it to citizens. The international agreement also, like UN Resolution, and other international laws, often taking the human rights value into account before exercising it. All of these facts highlighted that the Universal Human Rights is an important principle to be integrated within the global citizens.